A minimum of 5-year follow-up after lumbar transforaminal epidural steroid injections in patients with lumbar radicular pain due to intervertebral disc herniation - Kennedy, David J.; Zheng, Patricia Z.; Smuck, Matthew; McCormick, Zachary L.; Huynh, Lisa; Schneider, Byron J. (The spine journal, 2018)
Patients with lumbosacral radiculopathy from an intervertebral disc herniation are frequently treated by transforaminal epidural steroid injections (TFESIs). The long-term outcomes of these patients are poorly described. We aimed to determine the long-term outcomes for a homogenous group of patients with acute unilateral lumbar radicular pain due to single-level herniated nucleus after lumbar epidural steroid injection at ≥5 years. This is a prospective cohort study. Subjects enrolled into a previous reported multi-institutional randomized controlled trial, ≥18 years old with single leg radicular pain rating ≥4/10 for less than 6 months' duration, with radiographic imaging demonstrating an anatomically congruent single-level herniated nucleus pulposus. Presence of recurrent or persistent pain, pain within the previous week, current opioid use for radicular symptoms, additional spine injections for radicular pain, progression to surgery, and unemployment due to pain as determined by independent phone interview at least 5 years after enrolment due to the initial pain complaint were the outcome measures. All patients initially underwent a single-level lumbar TFESIs due to failure of conservative care, but could elect to pursue surgical intervention or repeat injections through shared decision making with the treating physician when and if pain control was deemed inadequate. After ≥5 years, an independent assessor contacted the subjects by phone and performed a standardized interview to determine outcomes. Fisher exact test was used to compare outcomes for those who pursued versus those who did not pursue surgery. During the recruitment period (December 2008 to December 2012), 78 subjects were enrolled. At 5 years, 39 (50%) of the 78 subjects were reachable for independent phone follow-up. Of these, 30 (76.9%, 95% confidence interval [CI] 61.7%–87.4%) had a history of recurrent pain since the initial TFESI. However, only 9 (23.1%, 95% CI 12.7%–38.3%) had current pain, while 3 (7.7%, 95% CI 2.7%–20.3%) were currently taking opioid medications. Nine (23.1%, 95% CI 12.7%–38.3%) had received additional TFESIs, and 19 (48.7%, 95% CI 33.9%–63.8%) had received surgery. Only 3 (7.7%, 95% CI 2.7%–20.3%) were unemployed due to related pain at time of follow-up. When comparing the group that had surgery versus those that did not, there were no differences in the rates of recurrent pain (16, 84.2% vs. 14, 70.0%, p=.81), current pain (6, 31.6% vs. 3, 15.0%, p=.47), opioid use (2, 10.5% vs. 1, 5.0%, p=1.00), rate of additional injections (6, 31.6% vs. 3, 15.0%, p=.47), or unemployment status (2, 10.5% vs. 1, 5.0%, p=1.00). Despite a high success rate at 6 months, the majority of subjects experienced a recurrence of symptoms at some time during the subsequent 5 years. Fortunately, few reported current symptoms, and a small minority required additional injections, surgery, or opioid pain medications. Lumbar disc herniation is a disease that can be effectively treated in the short-term by TFESI or surgery, but long-term recurrence rates are high regardless of treatment received.